Additional Small Dose of Prostaglandin F2α at the Time of AI Fails to Improve Pregnancy Rates of Lactating Dairy Cows - J. Stevenson; J. A. Sauls; L. Mendonca (Kansas Agricultural Experiment Station Research Reports, 2016)
In two experiments we tested the hypothesis that administering 10 mg of prostaglandin F2α(PGF) to lactating dairy cows concurrent with timed artificial insemination would increase pregnancy outcome. In three herds with 2,135 inseminations, we failed to demonstrate a positive effect on pregnancy per AI. Although a trend was observed in experiment 1, with more cows in experiment 2, the PGF treatment failed to improve pregnancy outcomes.
Keywords: prostaglandin; timed AI; pregnancy